A rede social TikTok e a erotização precoce de crianças e adolescentes: considerações à luz da hipervulnerabilidade do consumidor e da proteção integral à criança - Mosna, Arthur (2024)
Currently, it is known that the TikTok application is very popular among children and teenagers. However, by allowing unrestricted access to the application, children and adolescents become victims of early eroticization, due to the vast sharing of sexually explicit content on the platform. In this way, due to the aggravated state of vulnerability in childhood and adolescence, such individuals are easily persuaded to consume videos and create content on the platform, which can expose, in an eroticized way, the child's body. In view of this, this work seeks to position the issue of early eroticization in comparison with the rights and guarantees of children and adolescents in the Brazilian legal system, in order to expose the violation of these subjects' rights in the cyber sphere of the platform and strengthen the related discussion. to the rights of children and adolescents in the digital age, using as a scope the consumerist perspective of consumer hypervulnerability combined with the doctrine of comprehensive child protection.